6-Bromo-2-(4-chlorophenyl)-3-methyl-3H-imidazo[4,5-b]pyridine - Selma Bourichi; Youssef Kandri Rodi; Younes Ouzidan; Joel T. Mague; El Mokhtar Essassi; Hafid Zouihri (IUCrData, 2016)
In the title compound, C13H9BrClN3, the imidazopyridine fused-ring system is almost planar, with r.m.s. deviation of 0.006 (19) Å, and makes a dihedral angle of 29.32 (8)° with the mean plane of the 4-chlorophenyl group. In the crystal, C—H...N hydrogen bonds link the molecules into chains propagating in the [100] direction. Weak intermolecular π–π interactions between the five- and six-membered rings of the 3H-imidazo[4,5-b]pyridine moieties of neighbouring molecules [centroid–centroid distance = 3.8648 (12) Å] further consolidate the packing into layers parallel to the ab plane.